2015
DOI: 10.1111/tpj.12865
|View full text |Cite
|
Sign up to set email alerts
|

Full‐length transcriptome sequences and splice variants obtained by a combination of sequencing platforms applied to different root tissues of Salvia miltiorrhiza and tanshinone biosynthesis

Abstract: These authors contributed equally to this work. SUMMARYDanshen, Salvia miltiorrhiza Bunge, is one of the most widely used herbs in traditional Chinese medicine, wherein its rhizome/roots are particularly valued. The corresponding bioactive components include the tanshinone diterpenoids, the biosynthesis of which is a subject of considerable interest. Previous investigations of the S. miltiorrhiza transcriptome have relied on short-read next-generation sequencing (NGS) technology, and the vast majority of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
264
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(278 citation statements)
references
References 38 publications
11
264
1
2
Order By: Relevance
“…PacBio yielded shorter assembled transcripts and sequence length was much improved on the Illumina platforms. This is in contradiction to the work of Xu et al (2015) in Salvia miltiorrhiza , which reported longer PacBio transcripts compared to Illumina, although this comparison was performed prior to CDS selection. On the contrary, Dong et al (2015) carried out a comparison in Triticum aestivum to determine length improvement of high quality (based on mapping rates) PacBio transcripts over previously annotated wheat gene models, and found minimal (45 nt on average) improvement.…”
Section: Resultscontrasting
confidence: 84%
See 2 more Smart Citations
“…PacBio yielded shorter assembled transcripts and sequence length was much improved on the Illumina platforms. This is in contradiction to the work of Xu et al (2015) in Salvia miltiorrhiza , which reported longer PacBio transcripts compared to Illumina, although this comparison was performed prior to CDS selection. On the contrary, Dong et al (2015) carried out a comparison in Triticum aestivum to determine length improvement of high quality (based on mapping rates) PacBio transcripts over previously annotated wheat gene models, and found minimal (45 nt on average) improvement.…”
Section: Resultscontrasting
confidence: 84%
“…PacBio produced the greatest number of splice variants, which is valuable given their role in regulating many biological processes in plant systems as well as the inability to accurately assess these in nonmodel systems. Recent studies in animal systems have benefited from long read technology for isoform detection (Thomas et al 2014; Treutlein et al 2014; Au et al 2013; Sharon et al 2013), while in plants (Dong et al 2015; Xu et al 2015), more efficient splice junction detection has been shown in technology comparisons (Li et al 2014b). The promise of moving away from de novo transcriptome assembly of short reads and relying on third generation technologies has been proposed (Martin and Wang 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The S. miltiorrhiza genome harbors a large number of genes encoding terpene synthases and P450 proteins of unknown function131518222324. Although RNAi has been proven as a highly-effective approach for identifying the enzymes responsible for particular steps of various secondary metabolite synthesis pathways17, a high frequency of non-specific gene silencing can occur wherein sequence homology promotes the degradation of non-target transcripts25.…”
mentioning
confidence: 99%
“…Salvia miltiorrhiza , commonly known as Danshen, is a widely used traditional Chinese medicinal plant; its roots are used to treat hyperlipidemia as well as cardiovascular and cerebrovascular diseases (Cui et al, 2015; Luo et al, 2015; Xu et al, 2015; Zhou et al, 2016). The recent decline in environmental conditions, especially the increased drought conditions in soil due to higher global temperatures, has resulted in a sharp reduction in the planting area and yield of S. miltiorrhiza (Wu et al, 2014; Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%